Modification of the triangulation technique for arthroscopy of the canine shoulder joint using a new target device - Lehmann, M.; Lehmann, K. (Veterinary and Comparative Orthopaedics and Traumatology, 2004)
A modified triangulation technique for arthroscopy of the canine shoulder joint to insert a working cannula in the caudal joint pouch is described. This technique is compared with the triangulation technique of Van Ryssen (10). With the modified triangulation the insertion angle for the working cannula into the caudal joint pouch was provided by a target device which was attached to the arthroscopic sleeve. Both methods were carried out on 60 dog cadavers and the differences were recorded in terms of various parameters: success (SUC), time (TI), number of trials (TR), position of the working cannula (POS), damage to articular cartilage (DAM), and force to remove the working cannula (FOR). The modified triangulation technique permits simpler, faster and less traumatic insertion of the working cannula into the caudal joint pouch.
Keywords: Target device; arthroscopy; canine; shoulder joint; triangulation